THE EFFECT OF AGE, SLEEP DURATION, LEARNING DURATION, AND COFFEE INTAKE ON SHORT-TERM MEMORY - Chandra, Huki; Istiqomah, Silvi; Purnama, Adhitya Rinda Wahyu; Rafsanjana, Sasotya Rigan; Rosyid, Ahmad Nur (Industrial Engineering Department, Faculty of Engineering, Universitas Brawijaya, 2023)
In the reality of life, learning requires a process of remembering. In the process of teaching and learning, memory is crucial. Sleep deprivation affects the process of remembering in learning. Memory is one of the important aspects that affect student performance in learning. In addition to sleep duration, the age factor can also affect short-term memory. This study wants to find out if age, sleep duration, and learning duration have an impact on short-term memory. This study incorporates elements of cognitive ergonomics because it measures short-term memory performance to assess how people process information and how they maintain it in their memory. The age variable has a significance value of 0.001. The coefficient value on the age variable is 0.303 and is positive. This positive value indicates that increasing student age will increase the value of short-term memory. This shows that the higher the age of the student, the higher the ability in short-term memory. The study participants comprised individuals in the 18-22 age group. The findings demonstrate a significant impact of age on short-term memory proficiency. Students of higher age groups have accumulated several years of academic experience and have effectively refined their ability to handle memory-intensive lectures through their senior years, thereby enhancing their short-term memory capabilities. Thus, new students should allocate additional attention to enhancing their short-term memory skills. Furthermore, the study reveals that students who consume coffee exhibit notably elevated levels of short-term memory, underscoring the considerable impact of coffee consumption in enhancing this cognitive skill among students.